2003
DOI: 10.2223/jped.1082
|View full text |Cite
|
Sign up to set email alerts
|

Chronic recurrent multifocal osteomyelitis of the mandible: report of three cases

Abstract: Artigo submetido em 12.03.03, aceito em 28.05.03. ResumoObjetivo: Relatar três casos de osteomielite crônica multifocal recorrente de mandíbula. A osteomielite crônica multifocal recorrente é uma doença inflamatória, com acometimento de um ou mais ossos, sem patógenos isolados nas áreas afetadas, sendo o envolvimento da mandíbula raramente descrito na literatura.Descrição: Caso 1 -paciente feminina, com 13 anos, após tratamento dentário evoluiu com dor mandibular e febre. A paciente foi tratada com antibiótico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…18 It has been suggested that there may be a relationship between primary chronic osteomyelitis of the mandible (including cases attributable to Actinomyces) and chronic, recurrent, multifocal osteomyelitis (CRMO) 19 or the synovitis, acne, pustulosis, hyperostosis, osteitis syndrome variant. 20 Cases of CRMO with bilateral mandibular involvement, without involvement of other bones, have been described. 20 Chronic osteomyelitis of the mandible and CRMO are both characterized by multiple recurrences and inconsistent responses to antimicrobial treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 It has been suggested that there may be a relationship between primary chronic osteomyelitis of the mandible (including cases attributable to Actinomyces) and chronic, recurrent, multifocal osteomyelitis (CRMO) 19 or the synovitis, acne, pustulosis, hyperostosis, osteitis syndrome variant. 20 Cases of CRMO with bilateral mandibular involvement, without involvement of other bones, have been described. 20 Chronic osteomyelitis of the mandible and CRMO are both characterized by multiple recurrences and inconsistent responses to antimicrobial treatment.…”
Section: Discussionmentioning
confidence: 99%
“…20 Cases of CRMO with bilateral mandibular involvement, without involvement of other bones, have been described. 20 Chronic osteomyelitis of the mandible and CRMO are both characterized by multiple recurrences and inconsistent responses to antimicrobial treatment. Cultures of bone are usually sterile in CRMO, but it is possible that mandibular cultures that grow Actinomyces are sometimes contaminated.…”
Section: Discussionmentioning
confidence: 99%
“…It is basically a benign fibro-osseous lesion that has to be distinguished from other similar lesions like Chronic sclerosing osteomyelitis, Fibrous dysplasia, Ossifying fibroma, and Paget's disease based on combined clinical, radiographic, and histological features , Jong-Ki et al 2013). Chronic sclerosing osteomyelitis which is primarily an inflammatory condition of the jaws usually present with cyclic episodes of remissions and exacerbations, associated with unilateral pain, swelling and most often shows a single area of diffuse sclerosis containing small, ill-defined osteolytic areas (Paim et al 2003). Whereas, florid cemento-osseous dysplasia is evident as lobulated opaque masses which is often surrounded by a characteristic radiolucent border and is evident in all the quadrants symmetrically.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the levels of complement components (C3 and C4), IgA and IgM do not change. 1,5,7,8,10 HLA-27 is positive in less than 30% of the patients. 1,9,11 Performing a biopsy is important to rule out other diagnostic hypotheses.…”
mentioning
confidence: 93%
“…Histological findings are nonspecific and often similar to those found in septic osteomyelitis, but with no evidence of infection by any microorganism. 1,[2][3][4][5][6][7][8][9][10] Imaging tests such as radiography, CT, magnetic resonance imaging (MRI) and scintigraphy are some of the diagnostic tools. The latter two are most commonly used to rule out other diseases and to detect asymptomatic sites employing whole body screening techniques.…”
mentioning
confidence: 99%